Epidemiological Situation on Natural Focal Infectious Diseases of Bacterial and Viral Etiology in 2012 in the Territory of Siberia and Far East, and Prognosis for 2013 - S. V. Balakhonov (Проблемы особо опасных инфекций, 2013)
Analyzed is the incidence rate as regards natural focal infections of bacterial and viral etiology. Displayed is the data on the performed laboratory diagnostics of these infections in the territory of Siberia and Far East in 2012 and forecast of the epidemiological situation development in 2013. Analysis is carried out based on the data received by the Reference Center for surveillance over natural focal infections at the Irkutsk Research Anti-Plague Institute, from Rospotrebnadzor Institutions of Siberian, Far-Eastern and Ural Federal districts, as well as reviews and prognoses on the current state of natural foci of infections available from Altay, Tuva, Chita, Khabarovsk and Primorsk plague control stations.